An unusual case of visual perseveration. Issue 3 (March 1981) - Cleland, P G; Saunders, M; Rosser, R
Abstract : A patient is described with an unusual type of visual perseveration caused by a right parietal infarct. The mechanism of visual perseveration is discussed with particular reference to the increased movement of the perseverated image which our patient described.